Protective effect of quercetin loaded on bifunctional periodic mesoporous organosilica against damage induced by irradiation on the male reproductive system - S. F. Mirtaheri; S. N. Mousavi; Z. Abdi; E. Hosseini; M. S. Seyed Dorraji; F. Kabiri Esfahani; M. Gholami (Journal of Materials Science: Materials in Medicine)
Abstract Preserving fertility is important in men under radiation therapy because healthy cells are also affected by radiation. Supplementation with antioxidants is a controversial issue in this process. Designing a biocompatible delivery system containing hydrophobic antioxidants to release control may solve these disagreements. Herein, a bifunctional periodic mesoporous organosilica (PMO) was designed to load quercetin (Quer) and its application was studied on damaged cells induced by irradiation on the male reproductive system. Quercetin-loaded on PMO significantly improved the length and width of the testis after irradiation compared to the Quer, alone (p < 0.001 and p < 0.001, respectively). Sperm viability was significantly higher in the Quer-loaded on PMO than Quer, alone after irradiation (p < 0.001). Irradiation significantly decreased the sperm count (p = 0.01), however, Quer and Quer-loaded on PMO could not increase them to the normal ranges. Quer alone and loaded on PMO significantly reduced the sperm with abnormal morphology after irradiation (p < 0.001). Quer alone, and loaded on PMO significantly increased daily production of sperm after irradiation (p < 0.001). The number of apoptotic cells significantly increased after irradiation (p < 0.001). After irradiation, Quer loaded on PMO significantly decreased the apoptotic cells compared to the irradiated (p < 0.001) and Quer, alone groups (p < 0.001). The novel synthesized PMO containing Quer reduced the side effects of irradiation on the male reproductive system. Graphical Abstract